ANALISIS PENENTUAN SEKTOR UNGGULAN KABUPATEN LANDAK - B21109069, ARIS ISMAIL (Jurnal Pembangunan dan Pemerataan, 2014)
This thesis entitled Determination Sector Analysis Featured Landak District. This study aims to identify potential sectors and sub-sectors in the Landak District area to be seeded in order to compete in the economy of West Kalimantan and map the sector growing and less developed economies as well as looking at the potential of using Klassen Typologi Landak District. The methodology used in this research is descriptive research. The type of data that will be used in this research is secondary data which sectoral GDP and GDP sectoral Landak District of West Kalimantan Province. Source of data obtained from the Central Statistics Agency (BPS) Landak District and the Central Bureau of Statistics of West Kalimantan Province. The period of analysis in this study was between 2007 to 2011. Processing of data is done with the help of Microsoft Excel 2007 software. Analytical tool used in this study, the Location Quotient (LQ), and analysis Typologi Klassen. LQ sectoral analysis results into a sector basis, namely agriculture sector and trade, hotel and restaurant , while the subsector which is the basis for there are six subsectors, namely food crops subsector, plantation crops, without the oil and gas mining subsector, subsector of food, beverages and tobacco, wholesale and retail trade subsector, and subsector rental building. The results of the analysis indicate that Klassen Tipology sector or subsector is relatively advanced sector and subsector is growing rapidly Plant Foodstuffs, Sub Plantation Crops, Forestry Subsector Subsector Food, Beverages & Tobacco, Wholesale & Retail Subsector Subsector Lease and Building. The results overlay of the two analyzes are combined analysis of LQ, and Tipology Klassen from all sectors there are four subsectors that are leading subsector Landak District, namely: food crops subsector, plantation crops, food subsector, beverages and tobacco , wholesale and retail trade subsector, and ​​lease the building subsector . Keyword; Sector Featured, Location Quotient (LQ), and analysis Typologi Klassen.